STRATEGI PENGENDALIAN BANJIR TERPADU DI SUB DAS MELAWI KALIMANTAN BARAT - Stefanus Barlian Soeryamassoeka; Danang Gunarto; Umar; Fiqih Rahmanto; Riyanda Nurcahyo (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2023)
As in Indonesia in general, the Melawi Sub-watershed, part of the Kapuas River Basin, is also experiencing an increasing frequency of flooding. Currently, flooding in the Melawi Sub-watershed occurs not only in urban areas but also in rural areas in the middle and upper reaches of the Melawi Sub-watershed. To reduce the impact of floods in the Melawi Sub-watershed, a comprehensive and integrated flood control and management effort is needed. Whole means taking an approach that sees the Melawi Sub-watershed as an inseparable unit, including the upstream, middle, and downstream parts. Integrated means that flood control and management are carried out by considering technical, environmental, social, economic, legal, and institutional aspects in and around the Melawi Sub Watershed. This research aims to create a concept that can be used and applied in minimizing flooding in the Melawi Sub Watershed to prevent the frequency of flooding in the Melawi Sub Watershed from increasing by creating an integrated flood control strategy from various sectors. The results of this study can be helpful for policymakers in West Kalimantan, especially Sintang Regency and Melawi Regency, in overcoming flood problems in the Melawi Subwatershed. This research used secondary data (rainfall data, maps, and information from previous studies) and primary data (soil sample data, Focus Group Discussion results) with geographic information system software and MS Excel for analysis. The spatial analysis shows that flooding in Melawi Sub Watershed mainly occurs due to land conversion for settlements, plantations, and mining.